Analisis kepatuhan penerapan protokol covid-19 pada masa adaptasi kebiasaan baru di masjid wilayah Pedurungan Semarang - Ichsan Hadipranoto; Widodo Widodo; Adita Puspitasari Swastya Putri (Jurnal SAGO Gizi dan Kesehatan, 2022)
Background: The implementation of the Covid-19 protocol is a form of the government effort to prevent and break the chain of transmission. The government seeks to optimize the implementation of the Covid-19 protocol, taking into account various joints and fields of community life such as socio-economics, culture, and religion. The Covid-19 protocol has been standardized in places of worship, one of which is the mosque for implementing congregational prayers. Its implementation and application received various responses from the mosque management and congregation. It can be influenced by various factors such as the level of knowledge, attitudes and behavior of the community.Objectives: The study aims to specifically describe the implementation and compliance level of the Covid-19 protocol in several mosques in the Pedurungan Semarang area.Methods: The design used in this observational study was cross-sectional and was conducted only with a descriptive approach. The study was conducted in several mosques in the Pedurungan Semarang area from April to June 2022. The sample was 150 people, taken by stratified random sampling from the congregation of each mosque. Data collection on knowledge, attitude and, behavior, compliance was carried out by direct interviews using a questionnaire and observation of the implementation of the Covid-19 protocol. Data processing was carried out by editing, coding, and tabulating. Data analysis was only carried out descriptively, and frequency distribution was.Results: The implementation of the COVID-19 protocol in the three mosques in the Pedurungan Semarang area has been quite good (32,7%), good (16,7%), and very good (36,0%), and when the three categories are combined into a good category, then 85,4% of the protocol implementation has been successful. The good and very good knowledge of the Friday prayer congregation of 44,0% has made them good at implementing the COVID-19 protocol. Meanwhile, attitudes and behaviors have a higher achievement (46,7%) towards the good and very good implementation of the COVID-19 protocol.Conclusion: The compliance of worshipers with the implementation of the covid-19 protocol in several mosques in the Pedurungan Semarang area is good. Of course, this is supported by the knowledge, attitudes, and behavior factors of those who prioritize and take covid-19 issues seriously. Mosque worshipers in the Pedurungan Semarang area very well practice mask application and hand-washing behavior.